2020
DOI: 10.1073/pnas.1917237117
|View full text |Cite
|
Sign up to set email alerts
|

Defects in nanosilica catalytically convert CO2to methane without any metal and ligand

Abstract: Active and stable metal-free heterogeneous catalysts for CO2fixation are required to reduce the current high level of carbon dioxide in the atmosphere, which is driving climate change. In this work, we show that defects in nanosilica (E′ centers, oxygen vacancies, and nonbridging oxygen hole centers) convert CO2to methane with excellent productivity and selectivity. Neither metal nor complex organic ligands were required, and the defect alone acted as catalytic sites for carbon dioxide activation and hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 44 publications
2
63
0
Order By: Relevance
“…Silica is ubiquitous in the Earth's crust and universally used, both in crystalline and amorphous forms, mostly for its surface properties. Silicas are used in industrial productions and processes, including ceramics, glass, paints, plastics, construction products, catalysis, nanofabrication, and biomedical applications, in which the surface assumes a fundamental role (9)(10)(11)(12). Some of us have recently shown that specific surface moieties of amorphous silica can catalyze amide bond formation, which has implications for prebiotic chemistry and the origin of life from silica minerals (13).…”
mentioning
confidence: 99%
“…Silica is ubiquitous in the Earth's crust and universally used, both in crystalline and amorphous forms, mostly for its surface properties. Silicas are used in industrial productions and processes, including ceramics, glass, paints, plastics, construction products, catalysis, nanofabrication, and biomedical applications, in which the surface assumes a fundamental role (9)(10)(11)(12). Some of us have recently shown that specific surface moieties of amorphous silica can catalyze amide bond formation, which has implications for prebiotic chemistry and the origin of life from silica minerals (13).…”
mentioning
confidence: 99%
“…Efforts to produce C 2 and higher products by utilizing the advantages provided by the defects present on the surface of TiO 2 are needed. Recent work by Chen et al 90 who reported the activation of CO 2 over defective Bi 2 O 3 for the production of the dimethyl carbonate using methanol, and Polshettiwar et al 91 who reported activation of CO 2 using defective dendritic fibrous nanosilica (DFNS) without any metal sites, could be a way forward for defect engineering in other catalytic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Even though not proved thoroughly yet, hollow pure silica structure may also demonstrate catalytic activity without any form of functionalization since it was revealed very recently that a highly porous defect‐containing nanosilica owns innate active sites (i. e., oxygen vacancies and nonbridging oxygen hole centers) which can drive chemical reactions such as CO 2 to methane conversion …”
Section: Discussionmentioning
confidence: 99%